2015
DOI: 10.5032/jae.2015.02122
|View full text |Cite
|
Sign up to set email alerts
|

Critical Theory View of the National FFA Convention

Abstract: Urban FFA members face unique challenges if they want to become active members in the National FFA Organization. FFA leaders have realized that the FFA organization does not represent the evolving demographics of America and have made efforts to cater to urban and diverse high school audiences with some success. This study seeks to explore this phenomenon from the perspective of urban and diverse agriculture students through the use of a critical theory lens. This paper focuses on one group of urban FFA member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…The significant findings of this study centered around two broad concepts: 1) expanding the knowledge base of agrarian ideology and 2) the process of working with conflicts around agricultural values between groups by determining how the conflict occurred and why. These finding are useful as education specialists in agriculture continue to work with diverse individuals, contexts, and value systems (Cano & Moore, 2010;LaVergne, Larke, Elbert, & Jones, 2011;Martin & Kitchel, 2015;Vincent, Killingsworth, & Torres, 2012). The findings indicated that students within these focus groups generally reaffirmed the differing agricultural ideology outlined in the conceptual framework.…”
Section: Discussionmentioning
confidence: 99%
“…The significant findings of this study centered around two broad concepts: 1) expanding the knowledge base of agrarian ideology and 2) the process of working with conflicts around agricultural values between groups by determining how the conflict occurred and why. These finding are useful as education specialists in agriculture continue to work with diverse individuals, contexts, and value systems (Cano & Moore, 2010;LaVergne, Larke, Elbert, & Jones, 2011;Martin & Kitchel, 2015;Vincent, Killingsworth, & Torres, 2012). The findings indicated that students within these focus groups generally reaffirmed the differing agricultural ideology outlined in the conceptual framework.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, students with a background in agriculture have been targeted for recruitment by higher education agriculture programs (Elliott & Lambert, 2018;Esters, 2007;Martin & Kitchel, 2015a), but because of an increasingly urban population and interest in equitable access for all students, there is interest in agriculture in urban settings (Bird, Tummons, et al, 2013;Brown & Kelsey, 2013;Martin & Kitchel, 2015b;Rubenstein et al, 2016). Moving into urban agriculture necessitates addressing the interests and issues from a more diverse racial and ethnic student body (Elliott & Lambert, 2018;Martin & Kitchel, 2015a). Even though SBAE leaders have tried to recruit and retain a diverse population of students, teachers, and college faculty, they have failed to keep the levels as high as necessary to meet demand (LaVergne, 2011;Smith & Baggett, 2012).…”
Section: The Need For Incorporating a Critical Pedagogy Of Agriculturementioning
confidence: 99%
“…Importantly, this process should not be passed over if a program does not serve students of color; a critical pedagogy of agriculture approach serves all students by examining injustices and working to the betterment of everyone. Highlighting the historical cultural oppression in the FFA in the classroom without working to correct any current cultural barriers in the FFA (Elliott & Lambert, 2018;Martin & Kitchel, 2013;2015a;Phelps et al, 2012) would be incomplete.…”
Section: Theory To Practice: Creating a Critical Programmentioning
confidence: 99%
“…Despite this ongoing commitment to promoting inclusion, the Lesbian, Gay, Bisexual, Transgender, Queer (LGBTQ) community is frequently overlooked in agricultural education and remains understudied in agricultural education research. For example, sexuality is not included in the analysis in key papers that investigate diversifying the agricultural workforce (e.g., Hoover, 2016); agriscience classrooms (e.g., Denson, 2017;Alston et al, 2010;Roberts et al, 2009); nonformal agricultural education programs, such as FFA or 4-H (e.g., Martin & Kitchel, 2015;LaVergne, 2015;Lawrence et al, 2013); and postsecondary agricultural education (e.g., Esters, 2007). LGBTQ-specific analyses are omitted from research related to cultural proficiency (e.g., Turley, 2017); teacher attitudes towards diversity (e.g., LaVergne et al, 2011;Warren & Alston, 2007); diversity in secondary agricultural education (e.g., Luft, 1996); and culturally competent pre-service teacher preparation (e.g., Talbert & Edwin, 2008;Wakefield et al, 2006).…”
Section: Introductionmentioning
confidence: 99%